Antifibrinolytics in liver surgery - Makwana, Jalpa (Medknow Publications, 2010)
Hyperfibrinolysis, a known complication of liver surgery and orthotopic liver transplantation (OLT), plays a significant role in blood loss. This fact justifies the use of antifibrinolytic drugs during these procedures. Two groups of drug namely lysine analogues [epsilon aminocaproic acid (EACA) and tranexamic acid (TA)] and serine-protease-inhibitors (aprotinin) are frequently used for this purpose. But uniform data or guidelines on the type of antifibrinolytic drugs to be used, their indications and correct dose, is still insufficient. Antifibrinolytics behave like a double-edged sword. On one hand, there are benefits of less transfusion requirements but on the other hand there is potential complication like thromboembolism, which has been reported in several studies. We performed a systematic search in PubMed and Cochrane Library, and we included studies wherein antifibrinolytic drugs (EACA, TA, or aprotinin) were compared with each other or with controls/placebo. We analysed factors like intraoperative red blood cell and fresh frozen plasma requirements, the perioperative incidence of hepatic artery thrombosis, venous thromboembolic events and mortality. Among the three drugs, EACA is least studied. Use of extensively studied drug like aprotinin has been restricted because of its side effects. Haemostatic effect of aprotinin and tranexamic acid has been comparable. However, proper patient selection and individualized treatment for each of them is required. Purpose of this review is to study various clinical trials on antifibrinolytic drugs and address the related issues like benefits claimed and associated potential complications.